Integrative model of conservation partnership in the context of community empowerment and ecosystem restoration in Baluran Situbondo National Park, East Java - Indri Fogar Susilowati; Tamsil; Mahendra Wardhana; Dita Perwitasari (Technium Social Sciences Journal, 2023)
Baluran National Park is a nature conservation area that has an original ecosystem managed with a zoning system that is used for research, science, education, supporting cultivation, tourism and recreation. Although Baluran National Park is used in accordance with laws and regulations, it is not free from problems. The problems faced are among others related to spatial planning ( zoning) of national parks, especially those related to special zoning, animal hunting, illegal logging, maximizing community involvement in national park management, regulations related to national parks. Problems can stem from the weak synergy of national park management carried out by the government and the community, resulting in conflicts related to the management of Baluran national park. Conflicts that occur in Baluran national park do not only involve the community around the national park, but if other parties are related to collaborative management of the national park itself. This research is needed to photograph and analyze the integrated model of conservation partnerships carried out by Baluran national park as one of the efforts to handle tenure conflicts and provide access for communities around the national park, in order to establish synergy in the empowerment of national parks, communities and the sustainability of Baluran national park. In addition, how the regulations that have been established can be the basis for implementing the use of Baluran national park to achieve the set goals.